Berberine nanoemulsion attenuates bisphenol A-induced metabolic impairment through NF-κB signaling in the liver of rat - Ali Hormozi; Hossein Salehi; Seyed Mohammad Ali Hosseini; Shahnaz Rajabi; Hamid Kabiri-Rad; Aatena Mansori; Tahora Fakhrtaha; Saeed Samarghandian; Tahereh Farkhondeh (Toxicology Reports, 2025)
This study was designed to investigate the potential of Berberine nanoemulsion (BNE) to mitigate Bisphenol A (BPA)-induced liver damage in rats. Thirty-six adult Wistar rats were randomly divided into six groups and exposed to various doses of BPA and BNE for 30 days. The experimental groups included a control group, a BPA-only group, BNE-only group, and combinations of BNE with BPA at 5 and 10 mg/kg doses. After 30 days of treatment, the rats were anesthetized, and blood and liver samples were collected. Key metabolic parameters, including glucose, triglycerides (TG), total cholesterol (TC), aspartate aminotransferase (AST), alanine transaminase (ALT) and alkaline phosphatase (ALP) and white blood cell (WBC) counts, were measured. Oxidative stress was assessed by measuring malondialdehyde (MDA) and nitric oxide (NO) levels. Gene expression analysis of NF-κB and IL-1β were performed using quantitative PCR. Liver histopathology was also conducted to assess structural alterations. BPA exposure significantly elevated serum glucose, TG, TC, AST, ALT and ALP levels, liver levels of oxidative stress markers (NO and MDA) and also expression of pro-inflammatory cytokines IL-1β and NF-κB compared to the control group. BNE treatment (10 mg/kg) significantly reduced blood glucose, TG, AST, ALT and ALP levels in BPA-exposed rats compared to non-treated BPA group. Additionally, BNE decreased liver levels of NO and MDA and normalized the total WBC count compared to the non-treated BPA group. The expressions of IL-1β and NF-κB were significantly reduced in the BNE-treated groups versus the non-treated BPA group. Histopathological examination of the liver revealed that BNE treatment alleviated BPA-induced liver damage, showing minimal structural alterations in the liver tissue. Our study demonstrates that BNE effectively mitigates the metabolic and inflammatory consequences of BPA exposure in rats. These findings contribute to understanding BPA toxicity and suggest the clinical potential of BNE in managing BPA-induced metabolic disorders in humans, warranting further investigation.